(untitled) (Revista Argentina de Cirugía, 2026)
Background: Acute appendicitis is one of the most common reasons for emergency departments visits and emergency surgery. In some cases, its diagnosis is still difficult. Objective: The aim of this study was to evaluate the performance of abdominal ultrasound in the diagnosis of acute appendicitis in a tertiary health care center. Material and methods: We conducted longitudinal study to evaluate the performance of a diagnostic test using data retrospectively collected. The population was made up of 113 patients [mean age: 24 years (range 3-90)], who consulted for pain in the right iliac fossa, underwent abdominal ultrasound and could be followed up until the results of the pathological examination were available between February 2016 and February 2018. The analysis included sensitivity, specificity, positive predictive value and negative predictive value of ultrasound for the diagnosis of acute appendicitis. Results: Ultrasound was positive for the diagnosis of appendicitis in 32 patients (28.3%) and was negative in 81 patients (71.7%). Fifty-three patients (46.9%) underwent surgery; 44 (38.9%) had confirmed appendicitis while the appendix was healthy in 9 patients (7.96%), and among these patients, the ultrasound had been negative for appendicitis. Sensitivity was 68.1%, specificity 97.1%, the positive predictive value was 93.7% and the negative predictive value 82.7%, with a false positive rate of 6.3% and a false negative rate of 17.2%. Conclusion: The results obtained coincide with those of the international literature and confirm that ultrasound is a useful tool for the diagnosis of acute appendicitis